Study on influencing factors of anthracycline-induced subclinical cardiotoxicity in DLBCL patients administered (R)-CHOP - Qian Dong; Wenxin Ou; Mei Wang; Tiantian Jiang; Yue Weng; Xi Zhou; Xiaoqiong Tang (BMC Cancer, 2022)
Abstract Background Anthracycline-induced cardiotoxicity is an irreversible cardiac cell injury. Therefore, it’s very important to identify influencing factors of anthracycline-induced subclinical cardiotoxicity (AISC). This study was designed to analyze the influencing factors of AISC in patients with diffuse large B-cell lymphoma (DLBCL) treated with the (R)-CHOP chemotherapy regimen. Methods This is an ongoing observational prospective clinical trial. All patients underwent conventional echocardiography and speckle tracking echocardiography at the time of enrollment and during treatment. Changes of global longitudinal peak systolic strain were assessed after 3 cycles of (R)-CHOP chemotherapy, and patients were divided into the AISC and No-AISC groups. Demographic data, clinical variables, and biochemical variables were measured. Regression models, receiver operating characteristic curve analysis, and difference values were used to explore the relationships between variables and AISC. Results Among 70 patients who completed 3 cycles of (R)-CHOP chemotherapy, 26 developed AISC. In multiple logistic regression, HDL-C (P = 0.047), ApoA1 (P = 0.022), TG (P = 0.029) and e’ (P = 0.008) were associated with AISC. The combination of HDL-C and NT-proBNP had the highest area under curves (AUC) for the diagnosis of AISC than HDL-C and NT-proBNP alone (AUC = 0.752, 95%CI: 0.63–0.87, P = 0.001). Between the No-AISC and AISC groups, there was no significant difference in HDL-C, ApoA1, and e’ at baseline and after 3 cycles of chemotherapy, respectively. The dynamic changes of HDL-C, ApoA1, and e’ from baseline to the end of the 3rd cycle of chemotherapy showed statistically significant differences. Conclusions HDL-C, ApoA1, TG, and e’ are independent predictive factors in DLBCL cases treated with the (R)-CHOP chemotherapy regimen. The combination of HDL-C and NT-proBNP may improve the predictive ability for AISC in patients with DLBCL administered 3 cycles of (R)-CHOP chemotherapy. Dynamic changes of HDL-C, ApoA1, and e’ may be meaningful for predicting AISC. Trial registration Our study was registered in the Chinese Clinical Trial Registry (Approval ID. ChiCTR2100054721 http://www.chictr.org.cn/showproj.aspx?proj=145082 ).